THE PRINTED HERITAGE OF YEGHISHE DURYAN, THE GRATEFUL PATRIARCH OF ARMENIAN JERUSALEM (Bulletin of Armenian Libraries, 2023)
The presentation discusses the period of service of Patriarch Yeghishe Duryan in Jerusalem (1921-1929), which became a   separate subject of study. Noteworthy is the fact that with the advent of Yeghishe Duryan (1860-1930) in the history of the monastery, a broad religious and intellectual movement unfolded, in which the publishing house didn’t stand aside. The unique works of the Armenian medieval bibliography, theological and historical memoirs of the Armenian Church, textbooks and translations were published. Based on the sources, it can be stated that the inspiring and educational activity of Patriarch Yeghishe Duryan was a great impetus, especially to the cultural field of the Holy See Congregation. The Duryanashen Trading Center was built with voluntary donations made on the occasion of his fiftieth anniversary (1929“in memory of the great patriarch and mentor.” The profits gained from the center were to be directed towards the publication of the “Durian” series.